Imperial Russian Academy at the End of XVIII — the First Half of the 19th Centuries (to the 235 Anniversary of Establishment of the Russian Academy) - G. N. Khrapkov (Управленческое консультирование)
This article is devoted to studying, the analysis and the characteristic of one of the first attempts undertaken in the Russian society of the end of XVIII — the first half of XIX centuries on a problem of preservation and development of language and literary heritage of the Russian Empire at the state level. The purpose of the work — on the basis of the studied sources and research to identify the structure, functions and responsibilities of members of the Academy, to note both the positive features and shortcomings in the activities of the established scientific body of the new model and to emphasize the need to apply its experience in solving a number of issues on the above problem for further work in this direction. In writing the article, the author used the following methods: system (analysis of the structure, duties of members of the Imperial Russian Academy, the results of their activities in this chronological period), historical and genetic (the desire to iden tify the main stages of the development of the Academy and its approaches to the execution of tasks, the purpose and the end result of which changed in accordance with the priorities that the Academy set itself at a certain stage of its existence). The result of this work was that the creation of the Academy was an attempt to show the need to preserve the native language and the creation of works written by its own authors, which in the future could become a very serious support in the field of education, including subsequent generations of the state. The results of the study allow us to draw attention to the need to apply the experience of the Russian Academy of modern power structures and experts of higher education engaged in solving the problems of the use of Russian language’s culture in the context of increasing the impact of technological progress on the development of modern Russian society.